2021
DOI: 10.1007/s10914-021-09590-5
|View full text |Cite
|
Sign up to set email alerts
|

Integrative Approach Uncovers New Patterns of Ecomorphological Convergence in Slow Arboreal Xenarthrans

Abstract: Identifying ecomorphological convergence examples is a central focus in evolutionary biology. In xenarthrans, slow arboreality independently arose at least three times, in the two genera of ‘tree sloths’, Bradypus and Choloepus, and the silky anteater, Cyclopes. This specialized locomotor ecology is expectedly reflected by distinctive morpho-functional convergences. Cyclopes, although sharing several ecological features with ‘tree sloths’, do not fully mirror the latter in their outstandingly similar suspensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 182 publications
(275 reference statements)
2
15
0
Order By: Relevance
“…The only metric with a significant correlation with body size for sloths is CSA, and most metrics have R -squared less than 0.05 ( Table 3 ). It is unclear whether this is due to the small body size range or the suspensory ecology of extant sloths, which results in unique loading of the vertebral column in sloths ( Nyakatura and Fischer 2010 ; Olson et al 2018 ; Alfieri et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The only metric with a significant correlation with body size for sloths is CSA, and most metrics have R -squared less than 0.05 ( Table 3 ). It is unclear whether this is due to the small body size range or the suspensory ecology of extant sloths, which results in unique loading of the vertebral column in sloths ( Nyakatura and Fischer 2010 ; Olson et al 2018 ; Alfieri et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The impressive diversity of extinct sloths could greatly increase the range of sizes and ecologies represented in the clade, allowing us to better examine the relationship between TBA, body size, and ecology within this group. There has been some examination of extinct sloth TBA, but not enough to provide any insight into how scaling or ecology impact the TBA of their vertebrae; these papers did not include sufficient data to use in our analyses ( Fariña and Blanco 1996 ; Per Christiansen and Fariña 2003 ; Brandoni et al 2010 ; Amson et al 2015 ; Montañez-Rivera et al 2018 ; Alfieri et al 2021 ). In particular, it would provide an excellent test of whether the unusual TBA properties of extant sloths is a characteristic of all folivorans, or one that stems from a suspensory lifestyle ( Amson et al 2017 ; Montañez-Rivera et al 2018 ; Alfieri et al 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Not only could the same diet habits lead to the convergent evolution of different species, but also the same living habits could lead to the eco-morphological convergence of different species. Previous studies found that there was eco-morphological convergence in slow arboreal xenarthrans through the analysis of multiple omics of the humeral and femoral internal structure [ 15 ]. Independently evolving species might lead to the convergent evolution of phenotypes in order to adapt to the same environment, but these convergent phenotypes do not necessarily result from convergent evolution at the molecular level.…”
Section: Introductionmentioning
confidence: 99%